KOMUNIKASI ANTAR BUDAYA MAHASISWA ETNIS TIONGHOA DENGAN MAHASISWA PRIBUMI DI FAKULTAS EKONOMI UNIVERSITAS RIAU - Ekasiv Prajnagaja; Nova Yohana (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
Culture and communication have a strong connection, its seen from the communication process of Chinese ethnic student with native student. Which Chinese ethnic student belonging to minorities, and they consider themselves to be different. So Chinese ethnic student tend to be closed to native student, Chinese ethnic student considered to be more excited to help the fellow ethnic, than to help help other native ethnic. This study aimed to analyze how the intercultural communication behavior of Chinese ethnic student with native student and to determine whether there are obstacles in the intercultural communication of Chinese ethnic student with native studentThe method in this research is qualitative method with symbolic interaction approach. A total f informants in this research are 11 people, 9 of them are Chinese ethnic student, and the 2 are from native student. The selection of informants is done by using snowball sampling technique. The process in analytical data technique are begin with data reduction, data presentation and then make a verification.The result of this research indicate that the process of verbal communication by the two sides is the Chinese ethnic students are trying hard to learn native language, and native student also trying to introduce local language to Chinese ethnic student. The form of non-verbal communication are shake head to show disagree, frowning to show confusion, and give a thumb up to show agreement. The obstacles that happens during communication process are language, stereotype and prejudice.Keywords : Intercultural Communication, Chinese Ethnic Student, Native Student